Liquidity Rules and Credit Booms - Hachem, Kinda; Song, Zheng (Journal of Political Economy, 2021)
This paper shows that liquidity regulation can trigger unintended credit booms in the presence of interbank market power. We consider a price setter and a continuum of price takers who trade reserves after the realization of idiosyncratic liquidity shocks. The price takers are endogenously less liquid and circumvent regulation by engaging in shadow banking, which leads to a reallocation of funding away from the more liquid price setter. This reallocation channel underlies the credit boom. Endogenous responses in bank liquidity ratios also affect the magnitude of the boom. We discuss extensions of the model and illustrate its quantitative performance with an application to China.